Hedging Power A Metadiscourse Analysis of Article Speeches in the Guardian - Al- Hussein, Zahraa Abdul; Sultan, Abbas H. J. (Indian Journal of Information Sources and Services, 2025)
The research examines the intentional use of hedges in political speeches, concentrating on the impact of these linguistic choices on message transmission and comprehension. It looks at how utterances of caution and certainty change the tone, the way the audience reacts, and the speaker’s perspective. The research delineates prevalent forms and frequencies of hedges, their application influenced by ideology, and their effects on the political setting. The qualitative technique uses language frameworks to categorise hedges, revealing that good combinations augment message impact and audience engagement.